Why Think? Just Do: The Dawn of a New Era in Australia and Implications for Australian LIS Research - Smith, Kerry (Faculty of Information Management, Universiti Teknologi MARA, 2011)
Work undertaken by the Australian Library and Information Association (ALIA) Research Committee for the Australian Research Council's (ARC) Excellence in Research (ERA initiative revealed a commitment by Australian library and information studies (LiS academics to undertake serious research for the profession in Australia, a necessity in order to survive in the current Australian research and university policy climate. Yet on a world scale, LIS research being undertaken by research academics and students in the Australian LIS context is not extensive. The paper describes the current context of research activity in Australian universities and outlines the ALIA ERA experience, the final outcome of which was, in the eyes of many, unfavourable to Australian LIS research community. It concludes by addressing the question; Is there room for optimism?